PENGARUH PENGUNGKAPAN ESG DAN AUDIT REPORT LAG TERHADAP MARKET REACTION (Studi Kasus pada Perusahaan yang Terdaftar di Indeks Kompas-100 Periode 2019-2021) - Fauzan Ghairil Admiral; Surya Raharja (Diponegoro Journal of Accounting, 2023)
This study aims to examine the effect of ESG disclosure and audit report lag on market reaction. This study has a dependent variable, namely market reaction with independent variables including ESG disclosure and audit report lag. This study uses secondary data derived from the financial statements of all energy sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The research sampling was carried out using purposive sampling method. A total of 64 companies were tested with details of 192 samples throughout the three-year research span. The analysis method used is multiple regression analysis method. The results of this study indicate that social disclosure has a negative effect, while environmental have a positive effect on market reaction while governance disclosure and audit report lag are found to have no effect.